PENGARUH KEPERCAYAAN PADA PIMPINAN, MUTASI DAN BUDAYA ORGANISASI TERHADAP MOTIVASI KERJA DAN KINERJA PEGAWAI DI BADAN PENDAPATAN DAERAH KABUPATEN JEMBER - Prasetyo, Arief Yudho; Sularso, Raden Andi; Handriyono, Handriyono (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2018)
The purpose of this study is to examine the influence of trust towards the leader, mutation, and organizational culture on work motivation and employee performance at Regional Revenue Board of Jember Regency. This is an explanatory research with the sample consists of 150 employees of Regional Revenue Board of Jember Regency. Data were analyzed using Structural Equation Modelling (SEM). Results show that trust towards the leader, mutation, and organizational culture have significant effects on work motivation; mutation and work motivation have significant effects on employee performance. However, trust towards the leader and organizational culture have no significant effects on the employee performance at Regional Revenue Board of Jember Regency. Keywords: Trust towards the Leaders, Mutation, Organizational Culture, Work Motivation, and Performance